Spouse's Coping In Caring For The Elderly With Dementia - Anung Ahadi Pradana; Junaiti Sahar; Henny Permatasari (Jurnal Kesehatan Prima, 2021)
Dementia is a condition that is still considered normal in the elderly by the general public. Dementia clients often experience hopeless situations that include feelings of helplessness, frustration with their surroundings, economic dependence on family members, and inability to socialize with other people. Most dementia clients are cared for at home by family members due to financial limitations and supportive health services. This research is qualitative research with a descriptive phenomenology approach. This research was conducted in the period November 2018 - May 2019 in the Bekasi City area and the number of participants obtained by the researchers was 10 people. The theme obtained by the researchers was how the coping mechanism carried out by the carer while caring for the elderly with dementia which was described in 3 themes, including care efforts made to heal a partner, activities taken to avoid boredom, and resources owned by caregivers. In addition, there is a need for socialization for the community about dementia and an increase in understanding for health workers who work within the scope of the health office as well as the development of dementia conditions that occur.